Particle flow and segregation in a giant landslide event triggered by the 2008 Wenchuan earthquake, Sichuan, China - L. M. Zhang (Natural Hazards and Earth System Sciences, 2011)
During the 12 May 2008 Wenchuan earthquake, a large landslide of approximately 30 million m3 occurred at Donghekou with a particle run-out distance of over 2000 m. This paper presents fascinating particle flow and segregation characteristics in the landslide process found through field investigation of changes in the soil particle size, density, and fabric along the particle movement paths. The soil particles experienced projection, long-distance flying, sliding, and rolling. Trajectory segregation, inverse grading, and particle crushing were found in the landslide event, which contributed to the heterogeneity of the soil deposits. In the initial deposition area, particles with larger diameters appeared to have flown longer. Materials from different sources mixed, forming more uniform debris. In the run-out area, the particle flow tended to cause large particles to travel further. However, particle disintegration and crushing led to more small particles along the movement paths and the observed characteristic flow distances of very large particles did not increase with the particle diameter, which is different from observations of an idealized granular mass flow.